Vegetation of Croatia: Phytosociological classification of the high-rank syntaxa - Skvorc, Zeljko; Jasprica, Nenad; Alegro, Antun; Kovacic, Sanja; Franjic, Jozo; Krstonosic, Daniel; Vranesa, Ana; Carni, Andraz (Acta Botanica Croatica, 2017)
Croatia is among the most ecologically diverse and floristically rich countries in Europe, with a great variety of communities. The vegetation elaboration according to the standard central European method was initiated in Croatia at the beginning of the 20th century. In previous overviews of Croatian vegetation, the number of classes and alliances was underrepresented in relation to the country’s floristic richness. Furthermore, the level of knowledge and the amount of available data varied greatly among the various types of vegetation. The aims of this paper are mainly to compile a stabile syntaxonomic list of classes, orders and alliances dominated by vascular plants in Croatia and to adjust Croatian vegetation to the new European syntaxonomic system (EuroVegChecklist). It introduces a consistent description of high-rank syntaxa in Croatian. In conclusion, the vegetation of Croatia comprises 66 classes, 121 orders and 201 alliances. The number of syntaxa shows vegetation diversity that is rather high compared to most other European countries; this is related to the high floristic richness and endemism. The list points out the obvious problems and gaps in our knowledge of vegetation in Croatia and can serve as a baseline for the future vegetation studies.